Assessing dosing errors in legacy and low dose tip ENFit® syringes. (29th October 2021) - Guha, Suvajyoti; Niswander, Wesley; Herman, Alexander; Antonino, Mark J.; Venkataraman Rao, Priya; White, Kathleen; Haugen, Shani; Vesnovsky, Oleg
Abstract: What is known and objective: To avoid misconnections between different medical devices, a unique standardized design of connectors (ENFit ® ) for enteral medical devices has been developed. It was expected that the syringes with these connectors will replace the pre‐existing syringes, henceforth referred to as legacy syringes. However, the changes in the connector's design led to concerns regarding dosing errors for low volume syringes (≤2 ml). Therefore, novel low dose tip (LDT) syringes were designed to address these concerns. These LDT syringes can connect with the standardized ENFit ® male connectors. Only a few studies have investigated dosing errors, and findings have largely been mixed. The objective of this report was to calculate the contributions of unavoidable dosing errors for LDT syringes, compare with legacy syringes and to suggest strategies to optimize dose accuracy for enteral applications. Methods: Studies performed with a limited number of syringes to date may not reflect the actual diversity of dosing error that can occur across syringe orientations, batches, manufacturers, medications, etc. A computer‐aided design software SolidWorks ® was used to calculate the dosing errors in 0.5 and 1.0 ml legacy syringe connectors and were compared with dosing errors in LDT syringe connectors with the same nominal volume. Influence of orientation during delivery, spillage and flushing on dosing error was also investigated. Results and Discussion: For 0.5 and 1.0 ml LDT syringes, in absence of medication in the moat area, the maximum dosing error will be ±5% when delivering 100% of nominal volume, which is also equal to the dosing error in 0.5 and 1.0 ml slip tip legacy syringes. However, with medication present in moat area, and with syringe reused during flushing, the LDT dosing error can range from 1% to 18% and 28% to 35% for 1.0 and 0.5 ml syringes, respectively. The corresponding dosing error for legacy syringes would be when the same syringe is used for flushing or when syringe disengages pointing vertically up. The corresponding dosing errors for legacy syringes could range from −7 to 12% and −9% to 19% for 1.0 and 0.5 ml syringes, respectively. Dosing errors for legacy and LDT syringes increase as the nominal capacity of syringe reduces, or when the dose delivered is lower than the nominal capacity of the syringe. What is new and Conclusion: For LDT syringes, dosing errors can be reduced by clearing the moat area of the syringe and by using a new syringe for flushing post‐delivery of medication. For legacy syringes, dosing errors can be minimized by ensuring the female connector points up during disengagement from the syringe post‐medication administration, and by using a new syringe for flushing. Abstract : For 0.5 mL and 1.0 mL low dose tip (LDT) syringes, in absence of medication in the moat area, the maximum dosing error will be ± 5 % when delivering 100 % of nominal volume, and equal to the dosing errors in 0.5 mL and 1.0 mL slip tip syringes. Dosing errors increase with presence of medication in moat area, with reduction in nominal capacity of syringe, or when dose delivered is lower than nominal capacity.